Peningkatan Daya Berkecambah dan Vigor Benih Padi Hibrida Melalui Invigorasi - Wahyuni, Sri (Jurnal Penelitian Pertanian Tanaman Pangan, 2011)
Seed of the rice hybrid generally is not fully filled, resulting in low seed quality. Study was conducted in 2009 at the Indonesian Centre for Rice Research, Sukamandi, aiming to determine the effect of seed invigoration methods on viability and vigor of hybrid rice seeds. The treatments consisted of two factors, namely: (A) initial quality of Hipa 5 seeds, i.e., low and moderate, and (B) 8 seed invigoration methods, i.e., no treatment (control); soaking in water for 48 hours; soaking in 1.0 Mpa PEG 6000 solution for 24 hours; soaking in 5 ppm GA3 solution for 24 hours; soaking in 10 ppm GA3 solution for 24 hours; 12 hours hardening, 24 hours hardening), and soaking in a solution mixture of GA3 10 ppm Kinetin + 15 ppm for 24 hours. The results showed that all seed invigoration treatments increased seed germinations by 1 to 8% and the seed growth rates by 0.7 to 4.3 %/24 hour in seeds of hybrid rice Hipa 5, either in the high initial quality seeds or in the low initial quality seeds. Soaking of the medium quality seeds in 10 ppm GA3 + 15 ppm kinetin solution resulted in the highest seed germination (89%). In the low quality seeds, treatments with GA3 and 15 ppm Kinetin also resulted in high seed germination (79%), equivalent to that of treatment with 24 hours hardening (78%). All seed invigoration treatments, except for soaking in water for 48 hours, increased length and dry weight of the seedling stem. The highest length of the stem was shown from seed soaked in 10 ppm GA3 solution (16.8 cm), whereas the highest stem dry weight was shown from seed soaked in a mixture of 10 ppm GA3 + kinetin 15 ppm solution (526 mg/seedling). Based on all variables evaluated, soaking seeds in 10 ppm GA3 solution or a mixed solution of 10 ppm GA3 + kinetin 15 ppm is considered effective invigoration treatment to improve vigor and growth of hybrid rice seeds.